If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x-23=7x+25
We move all terms to the left:
-5x-23-(7x+25)=0
We get rid of parentheses
-5x-7x-25-23=0
We add all the numbers together, and all the variables
-12x-48=0
We move all terms containing x to the left, all other terms to the right
-12x=48
x=48/-12
x=-4
| 2×3^x=162 | | n−4=2.5 | | 4(x-2)+1=17 | | x/50=25 | | y+2.1=8.1 | | 3/a=6/a+1 | | 2x+18=6x+46 | | 8x=3x+25= | | 3x+1.8=8 | | 12x-7=3x+38 | | 3(x-5)-16=-43 | | 6/4=24/(8+x) | | X=35x+1 | | z/10=17.4 | | 5x–18=2x+9 | | 2×(x+3)=22 | | 36/24=6/4x | | 2(2-h)-6=-5h | | 5y-3=2y+23 | | -5(x+4)-4=1 | | 2(x+)=x-4 | | 2(x-2)+9=-5x | | 42y=2=68 | | 10+2x=3x-8 | | 8x-4=+15 | | 4(x-5)+3=-37 | | 8x+6/5+4x-8/3=-22 | | 8k+4=-2+7k+4-k | | 5(2x+7=25 | | 8v-19=13 | | 5(x+1)+1=16 | | 2x-x+5=13 |